14th AIAA Aviation Technology, Integration, and Operations Conference 2014
DOI: 10.2514/6.2014-2704
|View full text |Cite
|
Sign up to set email alerts
|

Wetware, Hardware, or Software Incapacitation: Observational Methods to Determine When Autonomy Should Assume Control

Abstract: Control-theoretic modeling of human operator's dynamic behavior in manual control tasks has a long, rich history. There has been significant work on techniques used to identify the pilot model of a given structure. This research attempts to go beyond pilot identification based on experimental data to develop a predictor of pilot behavior. Two methods for predicting pilot stick input during changing aircraft dynamics and deducing changes in pilot behavior are presented This approach may also have the capability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Previous results have found that the GDE and LSEEF methods are fairly accurate in predicting longitudinal stick input from commanded pitch. 24,25 These results will discuss the accuracy of each of the three methods -GDE, LSEEF, and LSEBGF -to predict both pilot longitudinal and lateral stick input from the flight director's commanded pitch and bank attitudes. The results will also discuss how Γ, λ, and k 0 vary depending on controller adaptation time during each run's three segments: before failure, during failure, and after failure.…”
Section: Resultsmentioning
confidence: 99%
“…Previous results have found that the GDE and LSEEF methods are fairly accurate in predicting longitudinal stick input from commanded pitch. 24,25 These results will discuss the accuracy of each of the three methods -GDE, LSEEF, and LSEBGF -to predict both pilot longitudinal and lateral stick input from the flight director's commanded pitch and bank attitudes. The results will also discuss how Γ, λ, and k 0 vary depending on controller adaptation time during each run's three segments: before failure, during failure, and after failure.…”
Section: Resultsmentioning
confidence: 99%
“…For vehicle ground braking, especially, reference targets such as inclination of runway sidelines, near and far angle are important for pilot lateral control modelling, which are discussed in [12]- [14]. As for obtaining the pilot model parameters, different estimation methods are introduced in previous researches [15]- [18].…”
Section: Introductionmentioning
confidence: 99%